Debate on the Plan of Making Fiqh Waria : Framing Analysis in Online Media - Maghvira, Genta; Mardiana, Lisa; Syukri, Syukri (Jurnal The Messenger, 2020)
This research is an online media study about the phenomenon of waria (transgender) people in Indonesia. Okezone.com reports about plans to make Fiqh Waria. Fiqh is expected to be a reference for waria to perform religious rituals in Islam. Islam has different laws between men and women. Research using Robert N. Entman's Framing Analysis. According to Entman, framing is a selection process that highlights aspects: problem identification, causal interpretation, moral evaluation, and action recommendations. The results of the study mentioned that in identifying the problem, it was reported about the plan to make a special jurisprudence called Fiqh Waria. In causal interpretation, making fiqh is needed so that they can perform worship after gender changes. In moral evaluation, transgenders are considered to have the same right to perform worship rituals. In the recommended action, it was reported that if the fiqh would become religious jurisprudence that humanizes humans.